Rape Myth Acceptance: A Comparison of Military Service Academy and Civilian Fraternity and Sorority Students. Issue 5 (9th June 2016) - Carroll, Marjorie H.; Rosenstein, Judith E.; Foubert, John D.; Clark, M. Diane; Korenman, Lisa M.
Abstract : Although both the military and fraternities have been theorized to be characterized by norms and attitudes that serve to legitimize violence against women, no previous work has examined the potential similarity and differences in rape-supportive beliefs of these 2 environments or the people drawn to them. Further, the belief systems of women within these organizations have received little attention. As such, the current study sought to serve as an initial exploration of the rape-supportive belief systems of people drawn to these groups. Participants were recruited from students entering 2 military service academies (U.S. Military Academy, n = 1, 169, 1, 003 men, 166 women; U.S. Naval Academy, n = 1, 916, 1, 551 men, 365 women) and fraternities and sororities at a Midwestern university ( n = 393, 188 men, 205 women). All participants completed the Illinois Rape Myth Acceptance Scale–Short Form. Consistent with previous findings related to gender, men were more accepting of rape myths than women. Further, there was more variability in the levels of rape myth acceptance among military service academy and fraternity men than among military service academy and sorority women. Although across all groups the women expressed significantly lower levels of rape myth acceptance than the men, women and men from the United States Military Academy were more closely aligned in their beliefs than women and men from the other samples. Implications for sexual assault prevention education are discussed.